Hybrid wire - arc additive manufacture and effect of rolling process on microstructure and tensile properties of Inconel 718 - Zhang, Tao; Li, Huigui; Gong, Hai; Wu, Yunxin; Diao, Chenglei; Zhang, Xiaoyong; Williams, Stewart (Elsevier, 2021)
Wire - arc additive manufacture (WAAM) is suitable for Inconel 718 components due to its high deposition efficiency. However, large columnar dendrites decrease the mechanical properties and can cause severe mechanical anisotropy. Cold rolling and warm rolling through flame heating have been investigated to analyze their effects on microstructure and tensile properties compared to as-deposited WAAM material. Standard solution and double aging (SA), as well as homogenization followed by solution and aging (HSA) heat treatments were compared. The results show that the large columnar dendrites change to finer equiaxed grains 16.4 μm and 26.2 μm in size for warm and cold rolled alloy, respectively. This increases to 22.5 μm and 30.1 μm after HSA treatment. The microhardness and strength of rolled material increase significantly and the warm rolled material after HSA treatment exceeds that of the wrought alloy. While the as-deposited and cold rolled samples both show significant anisotropy, isotropic tensile properties are obtained for warm rolled plus HSA heat treated samples. Finer equiaxed grains with more dispersive distributions of γ' and γ" strengthening precipitation contribute to the superior mechanical properties for warm rolled material. For both the cold and warm rolled material, there was an elongation decrease due to precipitated particles, which also led to a trans-granular ductile fracture mode. The strengthening mechanism of the hybrid rolling process was analyzed and found to be related to work hardening, grain boundary strengthening, precipitated strengthening phases and the δ phase.
Keywords: strengthening mechanism; tensile properties; Wire - arc additive manufacture